The Effect Of Postpartum Yoga On Lochea Discharge And Decreased Fundus Uteri Height - Ni Putu Dian Ayu Anggraeni; Karunia Ekayani, Ni Putu; Sudarmi, Sudarmi; Jiwantoro, Yudha Anggit (Interest : Jurnal Ilmu Kesehatan, 2023)
Background: An abnormal involution process can cause the uterus to fail to return to normal and result in the uterine reduction process being hampered and post partum bleeding occurring. Postpartum yoga is effective in accelerating uterine involution, so that it can decreased the fundus uteri height. Aim of this study is analyzing the effect of postpartum yoga on lochea expulsion and uterine fundus decline.  Methods: Quantitative quasi-experimental design with a pre and post test approach with control group design. The population in this study were all normal postpartum mothers recorded in March – May 2021. The number of samples in this study was 19 people for each group or 38 people for two groups using a simple random sampling technique. Yoga was given from the first day to the seventh day postpartum. Analysis used Wilcoxon and Mann Whitney  Results: Data showed in the control group on day 1 and a p value of 0.328 on day 3 (p value > 0.005). The intervention group on day 5 and day 7 with a p value of 0.000 on day 5 and a p value of 0.001 on day 7 (p value < 0.005).  Conclusion:Yoga is effective decreased fundus uteri height. Post partum mothers are advised to do yoga regularly from birth until the 6th week.